Meningkatkan Kreativitas Matematik dan Kepercayaan Diri Siswa melalui Pembelajaran Humanistik Berbasis Pendidikan Matematika Realistik - Lia Rista; M. Ikhsan; Hizir Hizir (Universitas Syiah Kuala, 2016)
The purpose of this study was to determine the difference between the improvement of mathematical creativity and self-confidence of students after PMR-based humanistic learning based on student level (high, medium, and low), and interaction between the learning levels of students after application of humanistic learning with PMR based on mathematical creativity of students. This study used a purely experimental research with research design shaped in